PEOPLE’S SATISFACTION WITH THE STATE OF THE MARKET OF PSYCHOLOGICAL AND PEDAGOGICAL SUPPORT SERVICES FOR CHILDREN WITH DISABILITIES - Bolshakov, Sergey; Bolshakova, Julia; Mikhalchenkova, Natalya (Revista Inclusiones, 2020)
The article analyses the conditions shaping the state policy in education and the government programs laying down the conditions for the development of education and culture. On the example of sociological data, the factor of consumer satisfaction with the services in the market of psychological and pedagogical support for children with disabilities and additional education for children is examined. The indicators of respondents’ evaluation of the service market state are disclosed. The variation of respondents’ ratings is explored based on the example of differentiated audiences of the region, municipalities, and small and medium-sized cities of the Leningrad region, Russia.